The role of media in shaping public opinion on water security in Central Asia - oshanova, oryntay (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2026)
The main purpose of writing this article is identify the influence of the media on the discussion of water security issues in Central Asian countries. Currently, in these regions, issues of limiting water resources, climate change and bringing the transboundary nature of rivers to the fore have begun to be put on the agenda. In such conditions, the media should become a tool for promoting environmental education, influencing politics and mobilizing civil society. For this reason, based on the method of content analysis and the results of a sociological survey, the main trends in writing the topic of water security in the mass media of Kazakhstan have been identified. This article also shows that the development of environmental journalism and the improvement of media literacy among the population will be a prerequisite for a sustainable solution to water security problems. The practical significance of research work can be called the use of scientific conclusions and data in the course of research, as well as in writing scientific papers and projects on environmental topics.